THE MAIN PROVISIONS OF THE SPECIAL-MOTOR TRAINING IN GYMNASTICS - Fazilov Ilhomjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, gymnasts striving for the highest sports achievements at all stages of training should master only those elements and technical parts of movements that can and should be used for a long time, and information is highlighted for longer technical training.